Agonising over industrial relations: Bringing agonism and dissensus to the pluralist frames of reference. (April 2021) - Van Buren, Harry J; Greenwood, Michelle; Donaghey, Jimmy; Reinecke, Juliane
The construct of pluralism has allowed us to see a world where parties could pursue divergent interests, sometimes to the point of conflict, and still work together to realise goals. In response to changing models of employment that are threatening many of the values and interests core to workers and society, new readings of pluralism have emerged that we will argue oscillate between antagonism and consensus. In response, we proffer the concepts of agonism and dissensus as bridging different schools of pluralist thought. Our article commences with a review of affordances and limitations of new pluralism. We then introduce the political philosophy of Chantal Mouffe – in particular her conceptualisations of agonism and dissensus – and discuss how these have been employed in consideration of the employment relationship. Next we describe a case salient to our argument, the ready-made garment industry's stakeholder engagement responses to the Rana Plaza tragedy in Bangladesh, into which we bring an understanding of agonism with the possibilities of dissensual engagement. We conclude with our contribution, the development of a nuanced view of pluralism based on dissensus and agonism, which better accounts for the co-existence of cooperation and conflict.